Analysis of the growth of two maize cultivars under various combinations of inorganic and bio-fertilization - Hartanti, Dyah Ayu Sri; Yuliana, Anggi Indah (Universitas Trunojoyo Madura, 2024)
Enhancing maize plant growth can be achieved through the application of biofertilizers, inorganic fertilizers, and the use of appropriate cultivars. This study aimed to examine the effect of different dosage combinations of biofertilizers and inorganic fertilizers, as well as cultivar selection, on improving maize plant growth. The research was conducted from June to September 2024, in Sambirejo Village, Jogoroto Sub-district, Jombang Regency, at an altitude of 40 meters above sea level. The method used was a factorial randomized block design (RBD) with two factors: combinations of biofertilizer and inorganic fertilizer doses (P), and maize cultivars (K), with 3 repetitions. Observations included stem diameter, leaf area, and plant growth rate measured at 15, 30, 45, and 60 days after planting (DAP), as well as nitrogen (N) and phosphorus (P) uptake observed at 60 DAP. The results showed that the use of the ADV Jago cultivar, combined with 100% inorganic fertilizer and 10 ml of biofertilizer (P7), produced the most optimal leaf area at 60 DAP and plant growth rate from 45 to 60 DAP, while the use of the Hibrida P35 cultivar combined with 100% inorganic fertilizer and 10 ml of biofertilizer (P7) increased stem diameter at 15 DAP. The ADV Jago cultivar resulted in the most optimal leaf area at 30 DAP. Lower doses of inorganic fertilizer, 75% and 50%, combined with 10 ml of biofertilizer (P8 and P9) also resulted in stem diameter and leaf area that were not significantly different from the 100% inorganic fertilizer treatment.